Implantation metastasis from sigmoid colon cancer to rectal anastomosis proved by whole exome sequencing and lineage inference for cancer heterogeneity and evolution analysis: Case report and literature review - Yu, Guan Yu; Gao, Xian Hua; Xia, Li Jian; Sun, De Bin; Liu, Tao; Zhang, Wei (Frontiers in Oncology, 2022)
It was estimated that 70% of patients with colorectal cancer were found to have viable exfoliated malignant cells in adjacent intestinal lumen. Exfoliated malignant cells had been reported to implant on raw surfaces, such as polypectomy site, anal fissure, anal fistula, hemorrhoidectomy wound, and anastomotic suture line. Tumors at anastomosis could be classified into four groups: local recurrence, local manifestation of widespread metastasis, metachronous carcinogenesis, and implantation metastasis. However, all of the previous studies only reported the phenomena of implantation metastasis at anastomosis. No study had proved the origin of anastomotic metastasis by genomic analysis. In this study, a 43-year-old woman presented with persistent hematochezia was diagnosed as having severe mixed hemorrhoids. She was treated by procedure for prolapse and hemorrhoids (PPH), without receiving preoperative colonoscopy. Two months later, she was found to have sigmoid colon cancer by colonoscopy due to continuous hematochezia and received radical sigmoidectomy. Postoperative histological examination confirmed the lesion to be a moderately differentiated adenocarcinoma (pT3N1M0). Six months later, she presented with hematochezia again and colonoscopy revealed two tumors at the rectal anastomosis of PPH. Both tumors were confirmed to be moderately differentiated adenocarcinoma without lymph node and distant metastasis and were finally removed by transanal endoscopic microsurgery (TEM). Pathological examination, whole exome sequencing (WES), and Lineage Inference for Cancer Heterogeneity and Evolution (LICHeE) analysis demonstrated that the two tumors at the rectal anastomosis were probably implantation metastases arising from the previous sigmoid colon cancer. This is the first study to prove implantation metastasis from colon cancer to a distal anastomosis by WES and LICHeE analysis. Therefore, it is recommended to rule out colorectal cancer in proximal large bowel before performing surgery with a rectal anastomosis, such as PPH and anterior resection. For patients with a suspected implanted tumor, WES and LICHeE could be used to differentiate implantation metastasis from metachronous carcinogenesis.